COMMERCIAL BANKS OF THE REPUBLIC OF UZBEKISTAN ANALYSIS OF THE AUDIT PROCEDURE - Botirov Lazizbek Botirovich; Xayrullayev Utkir Ismailovich (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2025)
This article analyzes the economic essence, classification and assessment of the procedure for auditing commercial banks in the Republic of Uzbekistan . was discussed.